Evaluation of Trichoderma-based biopesticides against plant pathogens and agronomic crop response - RAHMAN, MEHJEBIN; BORAH, P K; BORA, L C; BORA, POPY (The Indian Journal of Agricultural Sciences, 2021)
Biopesticides are the part of bio-inputs driven agriculture, popularly define the success of organic agriculture, especially in northeast India. Even today, many of the disease causing pathogens (Fusarium oxysporum f. sp lycopersicum, Alternaria brassicae, Colletotrichum lindemuthianum, Rhizoctonia solani and Sclerotium rolfsii) are beyond their control with conventional management strategy. In the year 2019-20, an evaluation was carried out in the department of Plant Pathology, Assam Agricultural University, Jorhat, Assam where we collected as many 10 commercial formulations marketed widely as biopesticides, and observed the population of Trichoderma sp. ranging from 1.0×105 to 2.0×108 cfu/g, inclusive of two predominant species T. harzianum and T. viride. As many five formulations, viz. Biogreen, Biofor –PF2, Biolime, Bioveer, Biozium and Biozin-PTB were observed effective in suppressing the growth of these five pathogens upto 91.2-97.1% under challenge inoculation in-vitro studies, which corroborated the response on tomato and rice seeds with regard to germination and vigour index (I and II). Our studies warranted greater effectiveness of these formulations carrying multiple antagonists in addition to strong seed priming effectsof Trichoderma sp.